MAKNA MOTIVASI DALAM LAGU DIRI DARI TULUS (ANALISIS SEMIOTIKA FERDINAN DE SAUSSURE) - Rina Juwita; Khansa Yumna Abiyyu; Azra Zahra Cintami; Cindy Elysa; Fajar Ade Putra; Muhammad Rizky Aidil Fitri (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2022)
Tulus in his single entitled “Self” has a motivational meaning which contains a message about mental healthrelated to self love. This study aims to determine the meanings of motivation contained in the lyrics of the song